Origin and Evolution of Flavin-Based Electron Bifurcating Enzymes - Poudel, Saroj; Dunham, Eric C.; Lindsay, Melody R.; Amenabar, Maximiliano J.; Fones, Elizabeth M.; Colman, Daniel R.; Boyd, Eric S. (Frontiers in Microbiology, 2018)
Twelve evolutionarily unrelated oxidoreductases form enzyme complexes that catalyze the simultaneous coupling of exergonic and endergonic oxidation–reduction reactions to circumvent thermodynamic barriers and minimize free energy loss in a process known as flavin-based electron bifurcation. Common to these twelve bifurcating (Bf) enzymes are protein-bound flavin, the proposed site of bifurcation, and the electron carrier ferredoxin. Despite the documented role of Bf enzymes in balancing the redox state of intracellular electron carriers and in improving the efficiency of cellular metabolism, a comprehensive description of the diversity and evolutionary history of Bf enzymes is lacking. Here, we report the taxonomic distribution, functional diversity, and evolutionary history of Bf enzyme homologs in 4,588 archaeal, bacterial, and eukaryal genomes and 3,136 community metagenomes. Bf homologs were primarily detected in the genomes of anaerobes, including those of sulfate-reducers, acetogens, fermenters, and methanogens. Phylogenetic analyses of Bf enzyme catalytic subunits (oxidoreductases) suggest they were not a property of the Last Universal Common Ancestor of Archaea and Bacteria, which is consistent with the limited and unique taxonomic distributions of enzyme homologs among genomes. Further, phylogenetic analyses of oxidoreductase subunits reveal that non-Bf homologs predate Bf homologs. These observations indicate that multiple independent recruitments of flavoproteins to existing oxidoreductases enabled coupling of numerous new electron Bf reactions. Consistent with the role of these enzymes in the energy metabolism of anaerobes, homologs of Bf enzymes were enriched in metagenomes from subsurface environments relative to those from surface environments. Phylogenetic analyses of homologs from metagenomes reveal that the earliest evolving homologs of most Bf enzymes are from subsurface environments, including fluids from subsurface rock fractures and hydrothermal systems. Collectively, these data suggest strong selective pressures drove the emergence of Bf enzyme complexes via recruitment of flavoproteins that allowed for an increase in the efficiency of cellular metabolism and improvement in energy capture in anaerobes inhabiting a variety of subsurface anoxic habitats where the energy yield of oxidation-reduction reactions is generally low.